P066 Transmission of Neisseria Gonorrhoeae among men who have sex with men: an anatomical site-specific mathematical model and impact of mouthwash. (30th June 2016) - Zhang, Lei; Regan, David; Chow, Eric; Cornelisse, Vincent; Gambhir, Manoj; Hocking, Jane; Fairley, Christopher
Abstract : Background/introduction: Epidemiological data suggest that kissing may play a significant role in gonorrhoea transmission. Aim(s)/objectives: We developed a transmission model to explain anatomical site-specific prevalence of gonorrhoea among Australian men who have sex with men (MSM) and evaluate the population-level impacts of screening and the use of mouthwash as interventions in reducing its transmission. Methods: We constructed a gonorrhoea transmission model to estimate the per-act transmission probability. Using Monte-Carlo simulations, we constructed hypothetical scenarios to evaluate its population-level impacts. Results: We have previously reported the prevalence of pharyngeal, anal and urethral gonorrhoea as being 10.6% (95%CI 8.1–12.2%), 8.6% (6.7–10.4%) and 0.17% (0.02–0.24%), respectively, in Australian MSM. Calibrated to these data, the model-estimated per-act transmission probability for gonorrhoea was high for transmission from urethra-to-anus (46.0% [41.7–52.6%]) and from-urethra to-pharynx (49.6% [46.7–53.8%]). Although pharynx-to-pharynx transmission through kissing has only a transmission probability of 17.4% (16.0–21.0%), it accounts for nearly three quarters of the annual incident cases (74.6% [70.0–82.4%]). A substantial increase in gonorrhoea screening from the current 40% to 100% may only halve gonorrhoea prevalence in MSM. In contrast, the use of mouthwash with moderate efficacy (extra 1% bacterial load reduction/use) would further reduce the corresponding site prevalence to 2.4% (1.8%–3.7%), 2.2% (1.6–3.2%) and 0.02% (0.01–0.03%), whereas a high efficacy (extra 1.5% reduction/use) may achieve a scenario of close to elimination. Discussion/conclusion: Our results suggests that kissing may be the key driver of community prevalence. If antibacterial mouthwash is effective and widely used, it may contribute to controlling the gonorrhoea epidemic.